Stress corrosion cracking of a 60 MW steam turbine rotor. (May 2015) - Banaszkiewicz, Mariusz; Rehmus-Forc, Anna
Highlights: Finite element calculations and material tests were done to find the root cause of rotor cracking. Stress corrosion cracking was the root cause of blade grooves failure. Vulnerability to SCC was eliminated by reducing the proof stress and local notch stresses of the weld repaired grooves. Abstract: The paper presents a root cause analysis of a steam turbine rotor blade groove cracking. The scope of analyses included material testing and mechanical integrity calculations. In scope of material testing, fracture microstructure was assessed and basic mechanical property characteristics of the rotor discs were determined. In scope of integrity analyses, the stress fields in the blade grooves were calculated and the possibility of cracking due to different mechanisms was assessed. Both calculations and material tests confirmed the stress corrosion cracking to be the root cause of the rotor failure. This was a basis for proposing the rotor discs repair by overlay welding with a lower strength material and modifications to the groove geometry.